Cognitive Function in a Randomized Trial of Evolocumab - Giugliano, Robert P; Mach, François; Zavitz, Kenton; Kurtz, Christopher; Im, Kyungah; Kanevsky, Estella; Schneider, Jingjing; Wang, Huei; Keech, Anthony; Pedersen, Terje R; Sabatine, Marc S; Sever, Peter S; et al. (The New England journal of medicine, 2017)
To address concerns about cognitive decline with the use of PCSK9 inhibitors, automated neuropsychological testing was performed in patients who received evolocumab or placebo. Evolocumab was noninferior to placebo with respect to cognitive changes from baseline over 19 months.